A DNA tetrahedron-based composite and scaffold material for stem cell enrichment

By using a complex of functionalized DNA tetrahedral framework structure and hyaluronic acid hydrogel, the problem of poor stem cell enrichment effect in the prior art was solved, and efficient repair and safe treatment effect on craniomaxillofacial bone tissue defects was achieved.

CN118440936BActive Publication Date: 2025-03-18SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410542221.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-03-18
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

In the repair of bone tissue defects in the craniomaxillofacial bone tissue, it is difficult to effectively capture and enrich stem cells and cytokines, and there are problems such as ethical risks, insufficient activity and immune response.

Method used

A complex based on functionalized DNA tetrahedral framework structure and hyaluronic acid hydrogel is developed to control the spatial orderly distribution of multivalent ligands through topology, improve ligand-receptor binding affinity, thereby enhancing the effect of stem cell enrichment.

Benefits of technology

It has achieved efficient enrichment of stem cells and effective repair of bone tissue defects, reducing the risk of immune response and improving the therapeutic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118440936B_ABST
    Figure CN118440936B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of medical technology, and specifically relates to a composite and scaffold material for stem cell enrichment based on DNA tetrahedron. The present invention provides a functionalized DNA tetrahedron framework structure modified with nucleic acid aptamers. Furthermore, a composite for stem cell enrichment and a scaffold material made thereof are constructed by using the functionalized DNA tetrahedron framework structure and hyaluronic acid hydrogel. The composite and scaffold material of the present invention have a better enrichment effect on stem cells and have a good application prospect in the repair of craniomaxillofacial bone tissue defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical technology, and in particular relates to a composite and a scaffold material for stem cell enrichment based on DNA tetrahedron. Background Art

[0002] Bone tissue defects in the oral craniofacial region are a common clinical and social problem. Existing clinical techniques mainly use various bio-inert implants to provide mechanical support, but long-term implantation in the body as foreign bodies brings many side effects. Tissue engineering technology studies and develops bioactive alternative tissues to repair bone defects, but at this stage, the main clinical application is to use alternative materials as scaffolds to promote defect repair. However, for the other two core elements of tissue engineering, seed cells and cytokines, there are many problems in existing research and technology: 1. In vitro culture or allogeneic schemes have ethical and potential contamination risks; 2. Artificial synthesis or xenogeneic materials have insufficient activity and immune risks; 3. The autologous blood concentration scheme can obtain limited cytokines or cell components. Therefore, in the repair of bone tissue defects in the craniofacial region, although various advanced scaffold materials have emerged in an endless stream in materials science, the research and application focusing on the capture and enrichment of cells or cytokines are still in urgent need of breakthroughs in both theory and practice.

[0003] The currently widely used in situ stem cell enrichment technology based on inorganic nanoparticles or organic polymers is to effectively guide endogenous progenitor cells or stem cells to the site of injury and promote the repair of damaged tissue by compounding or cross-linking target-specific molecules (such as aptamers) to a variety of carriers (such as ECM, PCL scaffolds and hydrogels). However, the structure of these inorganic nanoparticles or organic polymers is not fine and regular enough, resulting in random distribution or disordered arrangement of ligands on their surfaces. This spatial and electrostatic interference may reduce the binding efficiency with specific receptors on target cells. Therefore, it is necessary to develop new carriers to improve the ligand-receptor binding affinity by topologically controlling the spatially ordered distribution of multivalent ligands.

[0004] DNA framework structure is a DNA nanomaterial with a wireframe structure constructed by DNA. Tetrahedral framework DNA (tFNA) has the characteristics of high yield, simple synthesis, and easy mass production. Its tetrahedral structure also provides a topological structure basis for various chemical modifications. At present, there are no literature reports on the use of DNA tetrahedral framework structure in in situ stem cell enrichment. There is an urgent need to develop materials containing DNA tetrahedral framework structure to have good stem cell enrichment effect, and then apply them to bone tissue defects in the oral craniomaxillofacial region. Summary of the invention

[0005] In view of the problems of the prior art, the present invention provides a composite and a scaffold material for stem cell enrichment based on DNA tetrahedron.

[0006] A functionalized DNA tetrahedron framework structure is modified with 1-3 nucleic acid aptamers, and the nucleotide sequence of the nucleic acid aptamer is shown in SEQ ID NO.1.

[0007] Preferably, the functionalized DNA tetrahedral framework structure is formed by four single-stranded DNAs through base complementary pairing, and the nucleotide sequences of the four single-stranded DNAs are shown in SEQ ID NO.2-SEQ ID NO.5;

[0008] In the single-stranded DNA, 1-3 single-stranded DNAs are connected to the nucleic acid adaptor through complementary pairing of sticky ends. The nucleotide sequence of the single-stranded DNA after connecting the sticky ends is shown in SEQ ID NO.6-SEQ ID NO.8, and the nucleotide sequence of the nucleic acid adaptor after connecting the sticky ends is shown in SEQ ID NO.9.

[0009] The present invention also provides a DNA tetrahedron-based complex for stem cell enrichment, which is a hydrogel made of hyaluronic acid and the above-mentioned functionalized DNA tetrahedron framework structure;

[0010] In the hydrogel, the concentration of hyaluronic acid is 0.8wt.%-1.5wt.%, and the concentration of the functionalized DNA tetrahedral framework structure is 0.8-1.5μM.

[0011] Preferably, the connection method of the hyaluronic acid and the functionalized DNA tetrahedral framework structure is: reacting hyaluronic acid with methacrylic anhydride to obtain methacrylylated hyaluronic acid; inserting thiol groups into the functionalized DNA tetrahedral framework structure; and utilizing methacrylylated hyaluronic acid to react with thiol groups in the functionalized DNA tetrahedral framework structure to obtain.

[0012] Preferably, the molar ratio of hyaluronic acid to methacrylic anhydride is (2.5-3.5):5;

[0013] The method for connecting the functionalized DNA tetrahedron framework structure to the thiol group is to chemically connect the thiol group to the 5' end of any single-stranded DNA constituting the functionalized DNA tetrahedron framework structure.

[0014] Preferably, the method comprises the following steps:

[0015] Step 1, reacting hyaluronic acid with methacrylic anhydride to obtain methacrylylated hyaluronic acid;

[0016] Step 2, preparing a functionalized DNA tetrahedral framework structure with thiol groups connected thereto;

[0017] Step 3, reacting the methacrylylated hyaluronic acid with the functionalized DNA tetrahedral framework structure connected with thiol groups to obtain.

[0018] Preferably, in step 1, the reaction pH is 7.5-8.5, the reaction temperature is 0-4°C, and the reaction time is 8-12h;

[0019] In step 3, the reaction is carried out under the action of a photoinitiator, wherein the photoinitiator is selected from at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate or 2959 photoinitiator, and the reaction is irradiated with light at 360-370 nm for 30-60 seconds.

[0020] The present invention also provides use of the above-mentioned complex in preparing a material for enriching stem cells and / or repairing bone tissue defects.

[0021] Preferably, the material is used to repair bone tissue defects in the oral craniomaxillofacial region.

[0022] The invention also provides a bracket material, which is made by photocuring the composite.

[0023] The present invention utilizes a functionalized DNA tetrahedron framework structure and a hyaluronic acid hydrogel to construct a complex for stem cell enrichment and a scaffold material made thereof. On the one hand, the functionalized DNA tetrahedron framework structure of the present invention has the effects of anti-inflammatory, anti-oxidation, and relief of acute injuries, and has a therapeutic effect on craniomaxillofacial bone tissue defects; on the other hand, by topologically controlling the spatially ordered distribution of multivalent ligands, the functionalized DNA tetrahedron framework structure of the present invention can improve the ligand-receptor binding affinity and enhance the effect of stem cell enrichment, thereby making it have a better repair effect on bone tissue defects. It can be seen that the complex and scaffold material provided by the present invention have good application prospects in stem cell enrichment and craniomaxillofacial bone tissue defect repair.

[0024] Obviously, according to the above contents of the present invention, in accordance with common technical knowledge and customary means in the art, without departing from the above basic technical ideas of the present invention, other various forms of modification, replacement or change may be made.

[0025] The above contents of the present invention are further described in detail below through specific implementation methods in the form of embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies realized based on the above contents of the present invention belong to the scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1: Design and verification of functionalized DNA tetrahedral framework structure (Apt19S-tFNA). (A) Schematic diagram of functionalized DNA tetrahedral framework structure. (B) Molecular dynamics simulation shows stable formation of T3. (C) Fluorescence gel electrophoresis confirms the synthesis of T1, T2 and T3. (D) Cryo-EM (right) shows the branching morphology of T3. (E) Schematic diagram of T1 and T3 binding to cell membrane. (F) Replacement with negative cells or nonsense sequence shows that the cell membrane binding efficiency of T3 is reduced, proving the binding specificity. (G) Magnetic cell sorting scheme based on T3. (H) Magnetic cell sorting based on T3: T3 mediates stable and efficient binding of magnetic beads to BMSC membrane. (I) Capture efficiency of various Apt 19S-tFNA for individual mesenchymal stem cells (BMSC) and rat gingival fibroblasts (rGF). (J)-(K) Capture efficiency of various Apt19S-tFNA for mixed BMSC and rGF cells. *P<0.05, **P<0.005, *P<0.0005.

[0027] Figure 2 :Apt19S-tFNA was loaded onto HA hydrogel to form a "stem cell trap" system (T3-HA). (A) Design of T3-HA hydrogel: thiol-modified T3 was connected to methacrylated HA by click chemistry. (B)(C) NMR and XPS analysis confirmed the conjugation of T3 with HAMA. (D) Fluorescent gel electrophoresis further verified the preparation of T3-HA. (E) Young's modulus of hydrogel. (F)-(H) In vivo degradation of Cy 5-labeled T3-HA in nude mice within 1-2 weeks. (I) Scale bar: 200μm. *P<0.05, **P<0.005, *P<0.005

[0028] Figure 3: In vitro evaluation of T3-HA. (A) Schematic comparison of the capture of complementary aptamers by T3-HA and Apt19S*3-HA: Multivalent aptamers in T3-HA show increased capture efficiency. (B) Cy 5-labeled Apt19S complementary sequence (Apt19S#) confirms that the capture efficiency of T3-HA is higher than that of Apt19S*3-HA. (C) Three-dimensional confocal fluorescence reconstruction reveals the uniform distribution of captured 19s# in T3-HA. (D) Replacement of the apt19s aptamer sequence in T3 with nonsense sequence leads to decreased capture by T3-HA, confirming the capture specificity of apt19s. (E) Schematic diagram showing that multivalent interactions improve cell membrane affinity. (F)(G) Capture efficiency of T3-HA in separate and mixed BMSC / rGF cells. (H)-(K) Quantitative statistical capture efficiency verification. (L) Schematic diagram of transwell assay. (M)(N) Transwell assay demonstrates cell recruitment effect. Scale bar: 200 μm. *P<0.05, **P<0.005, *P<0.0005.

[0029] Figure 4 :Evaluation of early stem cell recruitment in vivo by T3-HA. (A) Schematic diagram of maxillary defect model after rat skull and first molar extraction. (B)(C) T3-HA enriched more CD29 and CD44 positive multipotent stem cells in the defect sites of skull and alveolar bone 3 days after implantation (n=5); (D), (E) BrdU staining showed stem cell proliferation in skull and alveolar bone defects (n=5). (F)(1) Quantitative analysis (E). *P<0.05, **P<0.005, *P<0.0005, *P<0.00005.

[0030] Figure 5: Therapeutic evaluation of the T3-HA system. (A) Micro-CT scans at 1 and 2 months showed that T3-HA enhanced skull regeneration. (B) Evaluation method of T3-HA in alveolar defects, red arrows indicate alveolar bone loss at the extraction socket, orange indicates buccal alveolar ridge loss, and blue indicates lingual alveolar ridge loss. T3-HA can improve bone recovery at the extraction socket site, as shown by micro-CT results. (C)(D) Histological staining at 1 and 2 months after T3-HA application showed increased osteoblast activity and collagen within the skull and alveolar defects (labeled on the figure: letter B: new bone tissue letter F: fibrous tissue). (E)(F) Enhanced expression of Runx 2 and collegan1A indicates increased osteogenic activity caused by T3-HA. (G) Statistical analysis of skull micro-CT at 1 and 2 months. (H) Statistical analysis of maxillary micro-CT at 1 and 2 months. Scale bar: 200 μm. n=5. *: compared with saline; #: compared with HA; ▲: compared with T3-HA. * / # / ▲: P<0.05, * / # / ▲: P<0.005, * / # / ▲: P<0.0005. DETAILED DESCRIPTION

[0031] In the following examples and experimental examples, reagents and raw materials not specifically described are all commercially available products.

[0032] Materials and Reagents:

[0033] All DNA sequences or functionalized DNA sequences were synthesized, labeled, and purified by Shanghai Shenggong Biotechnology Co., Ltd. The company also provided TCEP Tris-(2-carboxyethyl)-phosphochloridate. The culture media used included Dulbecco's modified Eagle medium (DMEM), penicillin-streptomycin, fetal bovine serum (FBS), α-minimum essential medium (α-MEM), trypsin-EDTA, and phosphate-buffered saline (PBS; SH30256), DPBS, all purchased from Hyclone Laboratories, Inc. The rat aortic smooth muscle cell line (A7R5) was purchased from the cell bank of the Shanghai Institute of Cell Biology, Chinese Academy of Sciences. Polyformaldehyde was purchased from Biosharp Life Sciences. Hyaluronidase and EDTA decalcification solution were purchased from Servicebio. Gelred nucleic acid dye was provided by Beijing Solebow Technology Co., Ltd. Alkaline phosphatase staining kit, Alizarin Red S staining kit, 10×TBE, 50×TAE, cell membrane green fluorescence staining kit (beyotime C1993S) and cell membrane far-red fluorescence staining kit (beyotime C1995S) were all purchased from Bio-Di Biotech. TMAvidin Trial Kit, Dynabeads TM MyOne TM Avidin T1 and StemPro TM Accutase TM Cell separation reagents were provided by ThermoFisherScientific. Magnetic separators were purchased from Beaver Biomedical Engineering Co., Ltd. 561 secondary antibody, Alexa 594 secondary antibody and BrdU were purchased from Sigma-Aldrich Merck. Photoinitiator lithium phenolphthalein diacetate (LAP) was purchased from Suzhou Yongqunquan Intelligent Equipment Co., Ltd.

[0034] TM buffer: 50 mM magnesium chloride, 20 mM Tris(hydroxymethyl)aminomethane, pH adjusted to 8.0. Polyacrylamide gel electrophoresis (PAGE) buffer: 1×TBE, composed of: 1 mM ethylenediaminetetraacetic acid disodium salt (EDTA), 12.5 mM magnesium acetate, 40 mM Tris(hydroxymethyl)aminomethane, 40 mM boric acid, pH adjusted to 8.0. Binding buffer: (10 mM MgCl2 in DPBS, pH=7.4).

[0035] In the following embodiments and experimental examples, the modified or unmodified single-stranded DNA sequences involved are as follows:

[0036] The nucleotide sequence of the nucleic acid aptamer (SEQ ID NO.1) is as follows:

[0037] AGGTCAGATGAGGAGGGGGACTTAGGACTGGGTTTATGACCTATGCGTG

[0038] The nucleotide sequences of the four single-stranded DNAs are as follows:

[0039] S1 (SEQ ID NO. 2):

[0040] ATTTATCACCGCCATAGTAGACGTATCACCAGGCAGTTGAGACGAACATTCCTAAGTCTGAA;

[0041] S2 (SEQ ID NO.3):

[0042] ACATGCGAGGGTCCAATACCGACGATTACAGCTTGCTACACGATTCAGACTTAGGAATGTTCG

[0043] S3 (SEQ ID NO.4):

[0044] ACTACTATGGCGGGTGATAAAACGTGTAGCAAGCTGTAATCGACGGGAAGAGCATGCCCATCC

[0045] S4 (SEQ ID NO.5):

[0046] ACGGTATTGGACCCTCGCATGACTCAACTGCCTGGTGATACGAGGATGGGCATGCTCTTCCCG

[0047] Among them, the 5' end of S1 used to prepare the thiol-functionalized DNA tetrahedral framework structure is chemically connected with a thiol group (SHC6, which is a n-hexylthiol group):

[0048] SH-S1: 5'-SHC6-ATTTATCACCCGCCATAGTAGACGTATCACCAGGCAGTTGAGACGAACATTCCTAAGTCTGAA-3`;

[0049] The S1 5' end used to prepare the biotin-modified DNA tetrahedral framework structure is chemically linked with biotin:

[0050] Biotin-S1:5'-biotin-ATTTATCACCCGCCATAGTAGACGTATCACCAGGCAGTTGAGACGAACATTCCTAAGTCTGAA-3'

[0051] S2-S4 is connected by complementary binding of the sticky ends bb*. After the nucleic acid adaptor is connected to the sticky ends, the nucleotide sequence of bS2-bS4 is as follows:

[0052] bS2 (SEQ ID NO.6):

[0053] CTTCACACCACACTCCATCTATTACATGCGAGGGTCCAATACCGACGATTACAGCTTGCTACACGATTCAGACTTAGGAATGTTCG;

[0054] bS3 (SEQ ID NO.7):

[0055] CTTCACACCACACTCCATCTATTACTACTATGGCGGGTGATAAAACGTGTAGCAAGCTGTAATCGACGGGAAGAGCATGCCCATCC;

[0056] bS4 (SEQ ID NO.8):

[0057] CTTCACACCACACTCCATCTATTACGGTATTGGACCCTCGCATGACTCAACTGCCTGGTGATACGAGGATGGGCATGCTCTTCCCG;

[0058] The nucleotide sequence of the nucleic acid aptamer b*-Apt19S (SEQ ID NO.9) modified with sticky ends is as follows:

[0059] TAGATGGAGTGTGGTGTGAAGTTTAGGTCAGATGAGGAGGGGGACTTAGGACTGGGTTTTATGACCTATGCGTG.

[0060] The nucleic acid modified with biotin at the end is the ligand biotin-Apt19S, and the nucleotide sequence is as follows:

[0061] Biotin-Apt19S: 5'-biotin-AGGTCAGATGAGGAGGGGGACTTAGGACTGGGTTTATGACCTATGCGTG-3'

[0062] Nucleic acid aptamer Apt19S that binds complementary to Apt19S # The nucleotide sequence is as follows:

[0063] Apt19S # :5'-ACGCATAGGTCATAAACCCAGTCCTAAGTCCCCCTCCTCATCTGACCT-3'.

[0064] Example 1 Functionalized DNA tetrahedral framework structure

[0065] This embodiment provides four functionalized or non-functionalized DNA tetrahedral framework structures (named T0, T1, T2, and T3, respectively) with stem cell enrichment function, which are composed of four single-stranded DNAs through base complementary pairing, wherein the four functionalized DNA tetrahedral framework structures are modified with 0, 1, 2, and 3 nucleic acid aptamers, respectively.

[0066] The preparation method of T0, T1, T2 and T3 is as follows:

[0067] T0: Quantitative SH-S1, S2, S3, S4 were prepared as a 1 μM system. 1 μL of each single chain was added to 96 μL TM buffer. After thorough mixing, it was synthesized by a one-step method (95°C for 10 minutes, then cooled to 4°C for 20 minutes) and stored at 4°C.

[0068] T1: Quantitatively prepare SH-S1, S2, S3, bS4, and b*-19s into a 1 μM system. Add 1 μL of each single chain into 95 μL TM buffer, mix thoroughly, and synthesize using a one-step method (95°C for 10 minutes, then cool to 4°C for 20 minutes), and store at 4°C.

[0069] T2: Quantitatively prepare SH-S1, S2, bS3, and bS4 into a 1 μM system, and prepare b*-19s into a 2 μM system. Add 1 μL SH-S1, S2, bS3, and bS4 single chains and 2 μL b*-19s into 94 μL TM buffer, mix thoroughly, and synthesize using a one-step method (react at 95°C for 10 minutes, then cool to 4°C for 20 minutes), and store at 4°C.

[0070] T3: Quantitatively prepare SH-S1, bS2, bS3, and bS4 into a 1 μM system, and prepare b*-19s into a 3 μM system. Add 1 μL SH-S1, S2, bS3, and bS4 single chains and 3 μL b*-19s into 93 μL TM buffer. Mix thoroughly and synthesize using a one-step method (95°C for 10 minutes, then cool to 4°C for 20 minutes) and store at 4°C.

[0071] Biotin-T3: Quantitative Biotin-S1, bS2, bS3, bS4 were prepared as a 1μM system, and b*-19s was prepared as a 3μM system. 1μL SH-S1, S2, bS3, bS4 single chain and 3μL b*-19s were added to 93μL TM buffer. After thorough mixing, they were synthesized by a one-step method (95℃ for 10 minutes, then cooled to 4℃ for 20 minutes) and stored at 4℃.

[0072] Example 2 DNA tetrahedron-based complex for stem cell enrichment

[0073] This embodiment provides a composite material that can be made into a scaffold material for stem cell enrichment.

[0074] The composite was prepared by the following method:

[0075] 5 g HA (MW = 94 wDa,) and 8.32 g methacrylic anhydride were dissolved in 50 mL deionized water. The pH of the mixture was adjusted to 8.0 using NaOH. The solution was stirred continuously on ice overnight. Afterwards, all reaction solutions were dialyzed for 3 days, and the dried products were collected by freeze drying to obtain methacryloyl hyaluronic acid (HAMA).

[0076] The functionalized DNA tetrahedral framework structure (T1 / T2 / T3, 1 μM) prepared in Example 1 was mixed with 1 wt.% HAMA. For every 100 μL of the mixture, 5 μL of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate photoinitiator (255 mM) was added. The mixture was then exposed to a 365 nm light curing lamp for 30 seconds to cure. After curing, it was washed three times with TM buffer ((10 mM Tris-HCl, 10 mM MgCL2, PH = 8.0)) to remove any unreacted materials.

[0077] The prepared samples were respectively named T1-HA, T2-HA, and T3-HA.

[0078] Comparative Example

[0079] In the following experimental examples, the control samples used and their preparation methods are as follows:

[0080] HA: Dissolve HAMA at 1% wt concentration using TM buffer. For every 100 μL of the mixture, add 5 μL of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate photoinitiator (255 mM). The mixture is then exposed to a 365 nm light curing lamp for 30 seconds to cure. After curing, wash three times with TM buffer ((10 mM Tris-HCl, 10 mM MgCL2, PH = 8.0)) to remove any unreacted material.

[0081] 19s*3-HA:

[0082] SH-apt19s (3 μM) was mixed with 1% HAMA. For every 100 μL of the mixture, 5 μL of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate photoinitiator (255 mM) was added. The mixture was then exposed to a 365 nm light curing lamp for 30 seconds to cure. After curing, it was washed three times with TM buffer ((10 mM Tris-HCl, 10 mM MgCL2, PH = 8.0)) to remove any unreacted material.

[0083] The technical solution of the present invention is further described below through experiments. The samples used in the following experiments are all prepared according to the methods of the above embodiments or comparative examples.

[0084] Experimental Example 1

[0085] 1. Experimental Methods

[0086] 1. Design, synthesis, and characterization of tFNA capture structures

[0087] 1.1. Design and synthesize tFNA structures with a side length of 21bp using Tiamat (a DNA material design program designed by Hao Yan's research group at Arizona State University). It is planned to load 1-3 Apt19S aptamer sequences on the vertices of tFNA to capture bone marrow mesenchymal stem cells. 1.2. Use coarse-grained DNA molecular dynamics tools such as Cando and oxDNA combined with all-atom molecular dynamics simulation to predict multiple structures, and optimize the design based on the prediction results.

[0088] 1.3. Synthesize different tFNA capture structures and combine characterization methods such as atomic force microscopy, transmission electron microscopy, and gel electrophoresis to clarify the yield, stability, and other structural chemical properties of tFNA structures of different scales and design details

[0089] 2. Verification of biocompatibility and microcirculatory stability of tFNA capture structure

[0090] 2.1. Synthesize tFNA capture structures containing 0-3 Apt19S sequences, explore and clarify the biocompatibility of different capture structures in representative cells of bone tissue defects (bone marrow mesenchymal stem cells, osteoblasts, etc.). Use CCK8 kit, cell apoptosis detection kit, live and dead cell staining, and cell morphology observation to clarify the biocompatibility of tFNA capture structure configuration and design.

[0091] 2.2. Synthesize tFNA capture structures containing 0-3 Apt19S, verify their stability in serum, DNA enzyme and other environments, and ensure that the tFNA basic capture structure has good microcirculation stability.

[0092] Enzyme and serum stability: First, the T3 structure in the T3-HA hydrogel was labeled with Cy5. Then, the labeled T3-HA hydrogel samples were divided into four groups and immersed in α-MEM basal medium containing 10U hyaluronidase, 100U hyaluronidase, 2% serum, and 10% serum, respectively. Four key time points were selected in the experiment: 1 day, 4 days, 7 days, and 14 days. Each sample group was tested twice: the first was imaging using TRIFM (Total Internal Reflection Fluorescence Microscopy, Leical). After imaging, the obtained images were analyzed using ImageJ software, the fluorescence intensity was measured, and the stability of the T3 structure under different conditions was evaluated. The second time was to weigh the hydrogel samples and monitor their weight changes in α-MEM basal medium containing 10U hyaluronidase, 100U hyaluronidase, 2% serum, and 10% serum, respectively, to evaluate the enzyme and serum stability of the T3 stem cell capture structure.

[0093] 3. Design, synthesis, and screening of cell capture and enrichment structures

[0094] 3.1. Optimize the tFNA structure using all-atom molecular dynamics tools. The all-atom model of the tFNA capture structure was constructed using the molecular dynamics tool Visual Molecular Dynamics 1.93, and the binding strength and capture efficiency of the target binding site were analyzed and quantitatively characterized. The tFNA capture structure was optimized by combining the coarse-grained molecular dynamics model (dissipative particle dynamics analysis).

[0095] 3.2. Use bone marrow mesenchymal stem cells as positive cells to screen the binding strength and capture efficiency of tFNA capture structures. Specifically, after the tFNA capture structure is synthesized, it is mixed with the bone marrow mesenchymal stem cell suspension for 10 / 30 / 60 min, and after the cells are precipitated by a centrifuge, the tFNA capture structure retained in the supernatant is quantitatively analyzed by high performance liquid chromatography, gel electrophoresis, etc., to determine the binding strength and efficiency.

[0096] Synthesis verification: After synthesizing T0, T1, T2, and T3, verify the synthesis of various DNA structures by polyacrylamide gel electrophoresis or agarose gel electrophoresis. Use AFM, TEM, ALS, or cryo-electron microscopy to confirm the successful synthesis of T0, T1, T2, and T3.

[0097] Membrane binding verification: When BMSCs reached 80-90% adherent density, cells were harvested using ACCUTASE cell separation reagent. After harvesting, cells were seeded at a density of 5 × 10^4 cells in 35 mm glass bottom culture dishes and incubated at 37 °C with 5% CO 2 The cells were incubated overnight under the conditions of . The next day, the cells were first washed with serum-free medium. Subsequently, the cells were incubated at 37°C for 30 minutes in serum-free medium containing T0, T1, T2, and T3 structures labeled with 250nM Cy5. After incubation, the medium was removed and washed three times with PBS. Then, the cells were incubated with DIO (2X) for 7 minutes to stain the cell membrane. After staining, they were rinsed three times with PBS. The treated cells were imaged using an Olympus FV3000 confocal laser scanning microscope. The fluorescence of Cy5 was excited at 640nm, the cell membrane stained by DiO at 488nm, and the cell membrane stained by DiD at 633nm. The distribution of DNA in the cell was determined based on the distribution of Cy5 fluorescence. It was determined based on the distribution ratio of the fluorescent nanostructures inside (or outside) the cell by comparing the fluorescence intensity inside (or outside) the cell with the total fluorescence intensity of Cy5 in the entire cell. The fluorescence intensity was calculated based on the grayscale value using ImageJ software. At least 50 cells were counted for each sample.

[0098] 3.3. The optimal tFNA capture structure (T3) after screening was combined with enrichment structures such as magnetic beads and HA hydrogels, and the yield, mechanical properties and stability of the structure were clarified using gel electrophoresis, high-performance liquid chromatography verification, immunofluorescence, Fourier transform infrared spectroscopy, etc.

[0099] Magnetic enrichment under different conditions: When BMSC / rGF cells reached 80-90% adherent density, cells were collected using ACCUTASE solution. Then, cells were stained with DIO for 7 minutes in serum-free medium and incubated at 37°C. After staining, cells were washed three times with PBS and resuspended in α-MEM. Cell density was determined using a hemocytometer.

[0100] Cells (1×10 4 ) were exposed to 750nM biotin-labeled Apt19S (biotin-Apt19S) and 250nM biotin-labeled T3 (biotin-T3) in DPBS binding buffer containing 10mM magnesium ions for 30 minutes. Then, magnetic beads with streptavidin were added and further incubated for 30 minutes at room temperature. After incubation, the cells were separated using a magnetic rack and washed three times. The cells were resuspended in 200μL of binding buffer and transferred to a confocal plate for imaging. All captured single cells were automatically imaged using a 488nm laser and then counted under a microscope. The capture efficiency was calculated as the ratio of the number of captured cells to the sum of the number of cells not captured in the supernatant.

[0101] In the mixed cell sample, the target cell BMSC was stained with DiO, while the non-specific cell rGF was stained with DiD. The 1:1 mixed cells were incubated with 750nM biotinylated apt19S and 250nM biotinylated T3 in binding buffer. After incubation, the cells were separated using a magnetic rack and washed three times. The cells were resuspended in 200μL of binding buffer and transferred to a confocal plate for imaging. All captured single cells were automatically imaged using a 488nm laser and then counted under a microscope. The capture efficiency was calculated as the ratio of the number of captured cells to the sum of the number of cells that were not captured in the supernatant.

[0102] The chemical structures of freeze-dried HAMA and T3-HA were analyzed using 1H NMR (400 MHz, DMSO-d6, δ) and X-ray photoelectron spectroscopy (XPS, Thermo Fisher K-ALPHA model). The water contact angle (WCA) of the sample surface was analyzed using a contact angle meter (OCA20, Dataphysics, Germany). The microstructure and morphological characteristics of the samples were observed using a scanning electron microscope (SEM).

[0103] 3.4. The effect of the capture and enrichment process on cell activity was evaluated through FDA / PI, CCK8, and cell apoptosis experiments.

[0104] 4. Validation of the performance of tFNA-based capture enrichment structures in in vitro and in vivo models

[0105] 4.1. In an in vitro cell model, the tFNA cell capture structure captured bone marrow mesenchymal stem cells or osteoblasts in blood or different cell suspensions, and enriched them through magnetic bead sorting and HA hydrogel system to verify the capture efficiency, capture specificity and the effect of the capture enrichment process on cell activity of the dynamic tFNA capture structure, and to verify the osteogenic ability of the collected cells.

[0106] In vitro validation of capture and enrichment: Specific molecule capture-z scan: Complementary sequence of Apt19S (Apt19S) at different concentrations (0uM, 3uM, 15uM, 30uM) # ) were mixed in DPBS binding buffer containing 10 mM magnesium ions and added to the HA, 19s*3-HA, and T3-HA groups. These mixtures were incubated on a shaker at room temperature for 30 minutes. Subsequently, they were washed three times with binding buffer to remove unbound Apt19S # For the incubated hydrogel samples, the fluorescence intensity was observed using a laser confocal microscope at 488 nm, and the distribution of apt19S in the hydrogel was observed using the z-axis imaging technique.

[0107] Cell capture: BMSCs were labeled with DiO, while RSCs were labeled with DiD. Subsequently, the labeled positive and negative cells were incubated with HAMA and T3-HA hydrogels, respectively. In order to simulate a mixed cell environment, positive and negative cells were mixed in a ratio of BMSC:RSC=1:1 and incubated with different hydrogels. All incubation operations were performed on a shaker at room temperature for 30 minutes. After incubation, the fluorescence of the hydrogel samples was observed using a confocal laser microscope. The number of cells was counted using Image software, and then the capture efficiency and specificity were calculated. The capture efficiency is defined as the ratio of the number of captured cells to (the number of captured cells + the number of uncaptured cells in the supernatant), while the capture specificity is the ratio of the number of positive cells to (the number of positive cells + the number of negative cells).

[0108] Transwell: A T3-HA hydrogel with a diameter of 4 mm and a thickness of 1 mm was placed in the lower chamber of the Transwell and supplemented with 10% α-medium. The upper chamber was filled with 200uL BMSCs with approximately 1x 10^5 cells. At 24, 48, and 72 hours, the Transwell was removed for subsequent processing. The retrieved Transwell was first fixed with 4% formalin. Subsequently, a cotton swab was gently used to wipe off the non-migrated cells in the upper chamber. The fixed cells were stained with DAPI staining solution for 10 minutes and then washed three times with PBS. The stained cells were observed and the number of BMSCs that migrated to the lower chamber was counted. The cell enrichment ability of the T3-HA hydrogel was evaluated based on cell counts at different time points and under different experimental conditions.

[0109] 4.2. After clarifying the in vitro application capability, a rat mandibular defect model was constructed. According to the defect morphology, 3D printing technology was used to customize the repair scaffold using the above-mentioned optimized functional hydrogel system (HA-tFNA). CT, section staining, mechanical evaluation, biochemical quantitative analysis and transcriptome sequencing were used to evaluate the application potential and corresponding biological mechanism of this capture enrichment structure in the bone injury rat model.

[0110] Animal modeling: 6-8 week old SD rats (male, n=5 per group) were anesthetized with 2% sodium pentobarbital, and then the hair on their heads was shaved and disinfected with medical iodine. An incision was made to expose the skull. For the post-tooth extraction skull defect model, under 2% sodium pentobarbital anesthesia, the oral cavity was disinfected with medical iodine, and then the first maxillary molar was extracted. Then, 15uL of saline (control group), HAMA (HA group, 1.0wt.%) and T3-HA (T3-HA group, HA: 1.0wt.%, T3: 1μM) were injected into the defect area, followed by photopolymerization for 30 seconds. After surgery, the wound was sutured and 2mL of gentamicin sulfate was injected. Then, the rats were placed on a heating pad to recover.

[0111] Early cell recruitment: After surgery, rats were intraperitoneally injected with BrdU solution at a dose of 100 mg / kg of body weight every day for three consecutive days. Two hours after the last injection, rats were perfused with 4% formalin under ether anesthesia. The skull and alveolar bones were extracted and fixed in 4% formalin for two weeks. After decalcification with EDTA solution, paraffin sections were made, followed by permeabilization with 0.3% Triton X-100, blocking with 3% bovine serum albumin, and incubation with primary antibodies. Subsequently, specific secondary antibodies were added and incubated at room temperature, followed by DAPI staining. Finally, fluorescence microscopy was used for observation and photography, and BrdU-positive cells were counted using Image J software.

[0112] Bone regeneration assessment: At 4 and 8 weeks after surgery, the rats were killed, and the skull and maxilla were collected and fixed in 4% formalin for two weeks. After that, micro-CT scanning was performed, and the data were analyzed using CTvox software. In addition, decalcification using EDTA solution was followed by paraffin sectioning, H&E and Masson staining, and IF staining, and analysis was performed using Image J software.

[0113] 2. Experimental Results

[0114] 1. Characterization of the tFNA capture structure (Apt19S-tFNA) and its binding ability to mesenchymal stem cells (BMSCs):

[0115] OxDNA simulations showed that in each Apt19S-tFNA, Apt19S stably bound to 1-3 vertices of tFNA ( Figure 1 B). Capillary and gel electrophoresis confirmed that T3 was successfully assembled with a yield of 80.4% ( Figure 1 C). Cryo-EM analysis revealed uniformly distributed nanoparticles or branched structures of T3 ( Figure 1 D). The above results show that the present invention successfully synthesized Apt19S-tFNA.

[0116] Cy5-labeled 19S-tFNA was incubated with ALPL-expressing bone marrow mesenchymal stem cells (BMSCs) for 30 min. Compared with T2 and T3, T1 exhibited lower binding affinity and higher internalization rate ( Figure 2 E). The same concentration of Apt19S was connected to the control (T3, T2 and T1) (i.e., the concentration of T3 was 250nM, the concentration of T2 was 375nM, the concentration of T1 was 750nM, and the concentration of Apt19S connected to the three was 750nM), showing a decreasing membrane binding efficiency of 93.45%, 87.06% and 63.35%, respectively. After replacing the Apt19S sequence in T3 with a nonsense sequence, the DNA tetrahedral framework structure could not bind to BMSCs ( Figure 1 F), confirming that T3 specificity depends on the Apt19S sequence. In addition, when co-incubated with rGF (rat gingival fibroblasts) and A7r5 (rat thoracic aortic smooth muscle cell line) with low ALPL expression, the membrane binding of T3 was reduced, further demonstrating the specific affinity of T3 for stem cells ( Figure 1 F).

[0117] To evaluate the binding efficiency and stability, the magnetic separation efficiency of various 19S-tFNA structures after binding to the cell membrane was evaluated. Biotin was introduced at the apex of tFNA to enable it to interact specifically with streptavidin-modified magnetic beads, thereby facilitating magnetic separation ( Figure 1G and 1H). After optimizing the number of magnetic beads, T3 increased the capture efficiency of BMSCs to 91.8% within 60 min. This is higher than the efficiency of non-clustered displayed aptamers such as T1 (one Apt19S attached to one tFNA) (about 70.4%), indicating that the clustered multivalent ligand controlled by the T3 structure (three Apt19S ligands equidistantly attached to one tFNA) has enhanced binding efficiency and stability ( Figure 1 I). In the mixed cell experiment, T3 selectively captured 88.6% of BMSCs, while rGF captured less than 20%, demonstrating extremely high binding efficiency and specificity ( Figure 1 J and 1K).

[0118] The above experimental results show that the Apt19S-tFNA prepared by the present invention has a strong specific binding ability to BMSCs.

[0119] 2. Characterization of T3-HA

[0120] By proton nuclear magnetic resonance spectroscopy ( Figure 2 B) and X-ray photoelectron spectroscopy (XPS) analysis ( Figure 2 C) confirmed the successful integration of T3 into HA. Gel electrophoresis showed a clear shift of Cy5-labeled T3-HA, further confirming the successful preparation of T3-HA ( Figure 2 D).

[0121] T3-HA hydrogels exhibited suitable Young's modulus and porous structure ( Figure 2 E). In degradation tests using hyaluronidase concentrations of 10U and 100U, and serum concentrations of 2% and 5%, T3-HA hydrogels showed gradual degradation over 14 days, with accelerated degradation at high concentrations. In in vivo studies performed on nude mice, using Cy5-labeled T3-HA and subsequent in vivo imaging, it was noted that the fluorescence intensity decreased from 100% to 56.7% within the first 4 days ( Figure 2 F and 2H), and the signal was almost gone by day 7. Anatomical evaluations performed during this period demonstrated the gradual in vivo degradation of the hydrogel, which maintained its morphology during the first week but began to lose its complete morphology in the second week ( Figure 2 G). Given these observations, the physical and mechanical properties of T3-HA hydrogels make them viable candidates for bone regeneration.

[0122] 3. In vitro evaluation of T3-HA

[0123] First, the complementary Apt19S sequence 19S # The capture efficiency ( Figure 3 A) In the lower 19S #At the same concentration, T3-HA showed an efficiency 2.55 times that of 19S3-HA loaded with Apt19S on HA ( Figure 3 B). This efficiency difference persists with increasing 19S# concentration, with T3-HA still being 2.09 times more efficient than 19S3-HA. 3D fluorescence scanning shows that the captured 19S# is evenly distributed in the hydrogel, indicating that the ligand is evenly distributed ( Figure 3 C). In the specificity test against the nonsense complementary sequence (Nonsense*), both 19S*3-HA and T3-HA showed reduced capture rate ( Figure 3 D) Taken together these results suggest that ordered multivalent ligand presentation increases the efficiency of recruitment of specific molecules.

[0124] In a separate cell capture experiment, the capture efficiency of T3-HA (89.05%) was higher than that of the disordered multivalent aptamer (62.8%) ( Figure 3 E-3J). In a mixed cell environment, T3-HA captured 89.9% of BMSCs and 18.2% of rGF ( Figure 3 G and 3K). In the transmembrane experiment, T3-HA hydrogel attracted more BMSCs than Apt19S*3-HA hydrogel, and cell migration increased 4.3-fold after 72 h ( Figure 3 These results suggest that multivalent ligand presentation based on tFNA clustering (three equidistant Apt19S ligands attached to tFNA) enhances local stem cell recruitment.

[0125] 4. Evaluation of early stem cell recruitment in vivo by T3-HA

[0126] To evaluate the in vivo stem cell enrichment efficacy of T3-HA, two different Sprague-Dawley rat bone defect models were used: a standard 4 mm cranial defect model and a maxillary defect model after first molar extraction ( Figure 4 A and 5B). The defects were treated with saline, HA hydrogel, and T3-HA hydrogel to assess their ability to recruit cells.

[0127] The early accumulation of stem cells is essential for bone defect repair because they have strong self-renewal and differentiation capabilities. Multipotent stem cells were identified by CD29 and CD44 markers. The T3-HA group displayed a higher number of CD29 and CD44 expressing cells than the defect group treated with saline, indicating an increase in multipotent stem cells ( Figure 4 B and 4F). This increase is particularly evident in the alveolar bone ( Figure 4 C and 4G).

[0128] BrdU is a thymidine analog that is commonly used to label proliferating cells to assess stem cell proliferation. On day 3 after treatment, the skull and maxillary tissues treated with T3-HA exhibited the highest number of BrdU-positive cells. In skull sections, the average count was 117 ± 15 per field of view, significantly exceeding the control group (33 ± 10) ( Figure 4 D and 4H; p<0.05). In alveolar bone sections, the number of BrdU-positive cells reached about 180±25, far exceeding that of the control group (52±16) ( Figure 4 E and 4I). These data confirm the enhanced proliferation capacity of stem cells in the T3-HA group, further supporting their effectiveness in stem cell accumulation and bone regeneration.

[0129] 5. Evaluation of the therapeutic effect of T3-HA system

[0130] Micro-CT scans of skull defects revealed significant differences in bone healing. One month after filling the maxillary defect with hydrogel, a gradual increase in bone volume was observed in the HA and T3-HA groups, while the control group did not show significant new bone formation. Quantitative analysis revealed that the T3-HA group exhibited significantly higher bone volume and new bone coverage, indicating its superiority in promoting skull regeneration in rats ( Figure 5 A and 5G). This trend continued at two months, with T3-HA hydrogels showing stronger bone regeneration, reaching 66.8% bone volume / total volume (BV / TV) ( Figure 5 A and 5G). After two months, the HA hydrogel showed limited healing, but the T3-HA hydrogel demonstrated enhanced regeneration, filling most of the defect area with new bone, as evidenced by a bone volume / total volume (BV / TV) of 66.8% ( Figure 5 A and 5G). One month after treatment, the T3-HA group showed significant new bone formation in the maxillary defect ( Figure 5 B), especially in the longitudinal sections of the extraction socket. Compared with saline treatment, it reduced the bone loss in the socket and the lingual alveolar ridge, showing effective bone regeneration ability ( Figure 5 H).

[0131] Figure 5 H&E staining in C showed that only a small amount of chaotically arranged new fibrous tissue appeared in the defect area in the control group even after 12 weeks. However, at 4 weeks, obvious newly formed bundles of fibrous connective tissue were observed in the T3-HA group, and further extended to the central area of ​​the defect after 8 weeks, forming obvious new bone tissue. In addition, Masson staining ( Figure 5C) The formation and maturation of bone tissue were evaluated. The defect site in the blank group was loose connective tissue. In contrast, in T3-HA, many immature collagens (blue areas) were observed at 4 weeks, and after 8 weeks, the area of ​​robust mature collagen (red areas) was further expanded. These results were consistent with the micro-CT data. Biomarkers of osteoblast precursor cells and new bone formation were also evaluated by immunofluorescence staining of Runx2 and Collegen1A (red). Significant positive expression was observed in T3-HA, indicating the effectiveness of T3-HA in promoting regeneration of bone defects ( Figure 5 E).

[0132] By integrating the results from the skull and maxillary defect models, it is clear that T3-HA hydrogel not only supports but also significantly enhances bone regeneration, especially in the maxillary defect after tooth extraction, where significantly better results were observed ( Figure 5 D and 5F).

[0133] The experimental results of these two models indicate that the T3-HA hydrogel provided by the present invention has a strong regenerative ability in different bone healing environments, especially showing remarkable performance in repairing maxillary bone defects after tooth extraction.

[0134] Through the above embodiments and experimental examples, it can be seen that the present invention provides a functionalized DNA tetrahedral framework structure complex and a hyaluronic acid hydrogel scaffold, which has an enhanced stem cell enrichment effect, so that it has a better repair effect on bone tissue defects. Therefore, the complex and scaffold material provided by the present invention have a good application prospect in stem cell enrichment and craniomaxillofacial bone tissue defect repair.

Claims

1. A functionalized DNA tetrahedral framework structure, characterized in that: The functionalized DNA tetrahedral framework structure is modified with 1-3 nucleic acid aptamers, and the nucleotide sequence of the nucleic acid aptamer is shown in SEQ ID NO.1; The functionalized DNA tetrahedron framework structure is formed by four single-stranded DNAs through base complementary pairing, and the nucleotide sequences of the four single-stranded DNAs are shown in SEQ ID NO.2-SEQ ID NO.5; In the single-stranded DNA, 1-3 single-stranded DNAs are connected to the nucleic acid adaptor through complementary pairing of sticky ends. The nucleotide sequence of the single-stranded DNA after connecting the sticky ends is shown in SEQ ID NO.6-SEQ ID NO.8, and the nucleotide sequence of the nucleic acid adaptor after connecting the sticky ends is shown in SEQ ID NO.

9.

2. A DNA tetrahedron-based complex for stem cell enrichment, characterized in that: It is a hydrogel made of hyaluronic acid and the functionalized DNA tetrahedral framework structure described in claim 1; In the hydrogel, the concentration of hyaluronic acid is 0.8wt.%-1.5wt.%, and the concentration of the functionalized DNA tetrahedral framework structure is 0.8-1.5μM.

3. The composite according to claim 2, characterized in that: The connection method of the hyaluronic acid and the functionalized DNA tetrahedral framework structure is: reacting hyaluronic acid with methacrylic anhydride to obtain methacrylylated hyaluronic acid; inserting thiol groups on the functionalized DNA tetrahedral framework structure; and utilizing the methacrylylated hyaluronic acid to react with the thiol groups in the functionalized DNA tetrahedral framework structure to obtain the hyaluronic acid.

4. The composite according to claim 3, characterized in that: The molar ratio of hyaluronic acid to methacrylic anhydride is (2.5-3.5):5; The method for connecting the functionalized DNA tetrahedron framework structure to the thiol group is to chemically connect the thiol group to the 5' end of any single-stranded DNA constituting the functionalized DNA tetrahedron framework structure.

5. The method for preparing the composite according to any one of claims 3 to 4, characterized in that: The steps include: Step 1, reacting hyaluronic acid with methacrylic anhydride to obtain methacrylylated hyaluronic acid; Step 2, preparing a functionalized DNA tetrahedral framework structure with thiol groups connected thereto; Step 3, reacting the methacrylylated hyaluronic acid with the functionalized DNA tetrahedral framework structure connected with thiol groups to obtain.

6. The preparation method according to claim 5, characterized in that: In step 1, the reaction pH is 7.5-8.5, the reaction temperature is 0-4°C, and the reaction time is 8-12h; In step 3, the reaction is carried out under the action of a photoinitiator, wherein the photoinitiator is selected from at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate or 2959 photoinitiator, and the reaction is irradiated with light at 360-370 nm for 30-60 seconds.

7. Use of the complex according to any one of claims 2 to 4 in preparing a material for enriching stem cells and / or repairing bone tissue defects.

8. The use according to claim 7, characterized in that: The material is used for repairing bone tissue defects in the oral craniomaxillofacial region.

9. A scaffold material, characterized in that: The composite material is prepared by light curing the composite material according to any one of claims 2 to 4.

Citation Information

Patent Citations

  • Non-vertex modified tetrahedral framework nucleic acid compound, preparation method thereof and application of non-vertex modified tetrahedral framework nucleic acid compound in promoting vascularization

    CN117838871A

  • Temperature-sensitive GEL material combination, preparation method therefor and use thereof

    US20230201424A1